Development of Instruments Performance Assessment Materials Singing for Students Junior High School in District Sambas Based on Android - M. Arvin Nugroho; Supriyadi Supriyadi; Wahyu Lestari (International Conference on Science, Education, and Technology, 2022)
Abstrak. This study aims to produce an android-based performance assessment instrument that is valid, reliable, and practical. Research development approach with ADDIE model from Dick and Carry. The performance assessment instrument developed consisted of: (1) task items, (2) music accompaniment audio, (3) an assessment rubric, (4) an observation sheet, and (5) guidelines for the interpretation of assessment results. Development of indicators of performance assessment instruments for the subject of singing folk songs by referring to the music learning curriculum for class VIII junior high school (SMP). Assessing students' competence in singing folk songs using performance assessment with practice test techniques with the assignment technique of singing folk songs in an unisono. Based on the resultunisonials conducted at the model application stage, shows that, technically, the performance assessment model on the subject of singing folk songs developed can be applied very well. Based on the results of the analysis of the reliability test conducted using the analysis of the correlation coefficient between classes, it shows that the instrument for assessing the performance of singing folk songs developed has met the specified criteria.